The Supremacy of Islamic Law in Conflict - Eujaaj , Sahib; Khalifa , Atiya (Islamic Sciences Journal, 2023)
ABSTRACT The most important matters that this research touched upon is that the laws, and in many of their rules, are taken from the rules of Islamic Sharia, especially the rules related to personal status and financial transactions, as many of those rules extracted from Islamic jurisprudence were collected by the legislator and turned into legal rules, presenting them in the form of a law. However, those who carried out the process of codifying the provisions of the laws and in some of the texts violated the provisions of Islamic Sharia, and here the judge collides with the issue of conflict between Islamic Sharia and the law when he is exposed to a case in which a legal text contradicts the provisions of Sharia. Islamic law and other laws are part of the provisions, which requires settling this dispute, and this is what this research has been exposed to.